1983
DOI: 10.1111/j.1744-7348.1983.tb02779.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Rhizobium inoculation and nitrogen fertiliser on nitrogen fixation and seed yield of dry beans (Phaseolus vulgaris)

Abstract: SUMMARYThe potential benefit to be derived from seed inoculation of Phaseolus vulgaris beans with effective strains of Rhizobium phaseoli, was investigated in field experiments over three years on a site low in soil nitrogen and lacking indigenous effective strains of R. phaseoli.Inoculation with R. phaseoli (strain RCR 3644) produced significant increases in nodulation, nitrogenase activity and plant growth in all experiments. In trials in 1978 and 1979, with cv. Seafarer, inoculation, in the absence of nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Saito (1982), Duque et al (1985), Weiser et al (1985), and Ramos and Boddey (1987) found no response to inoculation under field condition. By contrast, Taylor et al (1983) got yields as high as 3,000 kg ha' 1 with the introduction of effective strains of Rhizobium. These differences in N fixation and N assimilation indicated the occurrence of undetermined factors influencing the effectiveness of bean inoculation under natural conditions.…”
mentioning
confidence: 85%
“…Saito (1982), Duque et al (1985), Weiser et al (1985), and Ramos and Boddey (1987) found no response to inoculation under field condition. By contrast, Taylor et al (1983) got yields as high as 3,000 kg ha' 1 with the introduction of effective strains of Rhizobium. These differences in N fixation and N assimilation indicated the occurrence of undetermined factors influencing the effectiveness of bean inoculation under natural conditions.…”
mentioning
confidence: 85%
“…These estimates were insensitive to the level of mineral N in the previous October which was taken as 0. French bean was different from the other crops in that their associated Rhizobium (Taylor et al 1983), at Wellesbourne, could supply the crop with an amount of N equivalent of up to 60 kg ha −1 of fertilizer-N, an amount that decreased with increase in fertilizer-N. On this basis it was considered that the equivalent amount of N fertilizer (NR) provided by the Rhizobium was given by NR ¼ max 0:5 120 À NF ð Þ ; 0 f g ð 9Þ…”
Section: Model Inputsmentioning
confidence: 99%
“…Rhizobia inoculation of bean seed to facilitate nodulation and N2 fixation by the bean plant generally has not increased seed yield (Diatloff and Saint-Smith, 1981;Huntington et al, 1986;Weiser et al, 1985) although a few authors reported increased seed yield (Sparrow and Ham, 1983;Taylor et al, 1983).…”
Section: Introductionmentioning
confidence: 97%
“…Ranges of biologically assimilated N2 contributions were reported as 25 to 30 kg N ha -1 which amounted to 37 to 68% of the total plant N in Brazil (Ruschel et aL, 1982), 37-100kgNha -1 in U.K. (Taylor et al, 1983) and 40 to 125 kg N ha-t in Colombia (Graham and Rosas, 1977), and 40 to 121kgNha -~ in Canada which supplied about 50% of plant N (Rennie and Kemp, 1983).…”
Section: Introductionmentioning
confidence: 98%